Transplante hepático: percepções da pessoa idosa. - Andrade, Maria do Carmo de Farias (2020)
Until the middle of the 20th century, old age was seen as a period of physical and cognitive decline incompatible with development. With the aging of the population, scholars have come across another perspective on aging: active and healthy. From there, the Life Span Paradigm arises, which understands that human development occurs from birth to death. In Brazil and in the world, the population of elderly people is growing rapidly due to the accelerated reduction in mortality in all countries as a result of scientific discoveries, development of new technologies, better conditions of basic sanitation, among others, combined with the high birth rate in the two decades after World War II. Studies indicate that, in recent years, there has also been an increase in the number of elderly liver transplant recipients. Organ transplantation is considered an effective treatment for chronic and progressively disabling diseases, aiming to prolong and improve the patient's quality of life. The success achieved in this technique was possible thanks to advances in medical science. Many question the safety and effectiveness of liver transplantation for elders. The literature shows that the results are not related to chronological age, but to biological age. This study aimed to investigate the elderly's perceptions related to liver transplantation in regard to himself and his family. The specific objectives were: a) to investigate the perceptions of elderly liver transplant recipients regarding the diagnosis of the disease, going through the surgical procedure and up to current life; b) to understand the psychic coping strategies used by the elderly from the diagnosis of the disease to the present life; c) to analyze the perception of the transplanted elderly regarding the repercussions of the transplantation experience for his family; d) understand how the elderly assesses the importance of family support at the moment experienced. This is a qualitative study in which six elderly people (two women and four men) participated, aged between 60 and 73 years, who had undergone liver transplantation for at least six months and at most one year. The research project was approved by the University's Research Ethics Committee. The participants answered a sociodemographic questionnaire and a semi-directed interview focused on the research objectives. Data analysis was performed through Thematic Content Analysis. Six thematic categories emerged: 1) Discovery of the need for liver transplantation and reactions during the process in which the discovery of the disease and the need for transplantation was an unexpected situation and the element of surprise appeared in some statements; 2) Waiting for liver transplantation was characterized by anxiety and loss of quality of life; 3) Coping strategies while waiting for liver transplantation, in which the most used by the subjects was spirituality; 4) Transplant experience for the family from the perspective of the transplanted patient, in which they revealed that the transplant brought reflexes to the whole family dynamics; 5) Perception of the role of the family throughout the process from the perspective of the transplanted elderly person in which the family group was seen as the main source of support for the transplanted elderly person; 6) Current experience after liver transplantation in which most interviewees recognize that, after the transplant, there was an improvement in quality of life, despite the fact that they live with some restrictions.